2001
DOI: 10.1038/sj.bdj.4801235
|View full text |Cite
|
Sign up to set email alerts
|

The use of QLF to quantify in vitro whitening in a product testing model

Abstract: RESEARCHaesthetic dentistry to practitioners, many do not offer such procedures. Patients must therefore use 'at-home' products to achieve tooth colour change, typically through the removal of extrinsic stain. The majority of these products are marketed as tooth-whitening dentifrices.The causes of extrinsic tooth staining are complex and have been covered in the literature recently. 4 The method of action of these pastes is believed to be a combination of mechanical and chemical effects. 5 Research has assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Caries diagnostic devices using laser/light-induced fl uorescence detection systems, such as the DIAGNOdent 13-15 and QLF, [16][17][18] have been clinically studied, and promising results has been reported; 19,20 however, the mechanism of fl uorescent refl ection from carious lesions remains unclear. In this study, the relationship between the presence of intra-oral bacteria (S. mutans) and fl uorescence signals was investigated by using artifi cial demineralization models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caries diagnostic devices using laser/light-induced fl uorescence detection systems, such as the DIAGNOdent 13-15 and QLF, [16][17][18] have been clinically studied, and promising results has been reported; 19,20 however, the mechanism of fl uorescent refl ection from carious lesions remains unclear. In this study, the relationship between the presence of intra-oral bacteria (S. mutans) and fl uorescence signals was investigated by using artifi cial demineralization models.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Another type of fl uorescence device, quantitative light-induced fl uorescence (QLF), measures the fl uorescence induced by blue light illumination with wavelengths of around 405 nm. [16][17][18] It should be noted, however, that fl uorescence from carious lesions differs depending on the carious condition and that the primary origin of fl uorescence signals has not yet been fully determined.…”
Section: Introductionmentioning
confidence: 95%
“…34 Considerable interest surrounds the device and recent applications have included the assessment of decalcification adjacent to orthodontic brackets, dental erosion, tooth whitening, root lesions, and secondary caries. 30,[35][36][37] An investigation into the ability for QLF to determine plaque was conducted.…”
Section: Fluorescein Disclosing and Digital Plaque Image Analysis (Dpia)mentioning
confidence: 99%
“…QLF is an optical method that uses the natural fluorescence of teeth to distinguish between sound enamel and caries but it can also be used to detect stains in a similar manner. 15,16 There have been studies describing the detection of stain removal, although none have investigated the longitudinal monitoring of extrinsic stains. 15,16 This study has shown that QLF is an appropriate technique to longitudinally detect and quantify stain development and monitor bleaching in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The stain produced on the teeth when imaged using QLF has a similar appearance to demineralised lesions. By employing QLF it is possible to monitor and quantify longitudinally the analysis of stain and stain reduction on enamel.…”
Section: Qlf and Stainingmentioning
confidence: 94%